A Comparative Assessment of the Diagnosis of Swallowing Impairment and Gastroesophageal Reflux in Canines and Humans - Ullal, Tarini V.; Marks, Stanley L.; Belafsky, Peter C.; Conklin, Jeffrey L.; Pandolfino, John E. (Frontiers in Veterinary Science, 2022)
Swallowing impairment is a highly prevalent and clinically significant problem amongst both people and dogs. There are myriad causes of swallowing impairment of which gastroesophageal reflux is the most common. Due to similarities in anatomy and physiology between humans and canines, several swallowing impairment disorders affect both people and dogs. Examples include cricopharyngeus muscle achalasia, esophageal achalasia, hiatal herniation, and gastroesophageal reflux with secondary esophagitis and esophageal dysmotility. Accordingly, the diagnostic approach to human and canine patients with swallowing impairment is similar. Procedures such as swallowing fluoroscopy, high-resolution manometry, pH/impedance monitoring, and endolumenal functional luminal imaging probe can be performed in humans and canines. However, there are species differences that make the diagnostic assessment of canine patients challenging. Human patients can communicate their symptoms and respond to verbal directions. Dogs cannot and therefore, veterinarians must rely on clinical histories narrated by pet owners and physical examination findings. Dogs may also be unwilling to drink or eat and may be resistant to physical restraint during diagnostic procedures. Differences in nasofacial and esophageal anatomy amongst dogs also complicate the use of diagnostic equipment designed for humans. Despite the species differences and diagnostic challenges, dogs are a natural animal model for many human oropharyngeal and esophageal disorders, which presents a tremendous opportunity for shared learnings. This manuscript will review the comparative aspects of esophageal anatomy and physiology between humans and canines, summarize the diagnostic assessment of swallowing impairment in both species, and discuss future considerations for collaborative medicine and translational research.